FRI0074 Renal Dysfunction in Patients with Rheumatoid Arthritis: Results from the Comedra Study. (10th June 2014) - Couderc, M.; Soubrier, M.; Pereira, B.; Gilson, M.; Fautrel, B.; Pouplin, S.; Dernis, E.; Gossec, L.; Gaujoux-Viala, C.; Dougados, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) are at increased risk of renal dysfunction. Objectives: To assess the prevalence and associations of renal dysfunction in patients with RA. Methods: COMEDRA is a French nation-wide cross-sectional multicentric study on comorbidities in RA patients. Renal function was assessed by estimated glomerular filtration rate (eGFR) using the Modification of Diet in Renal Disease (MDRD) equation in patients from the COMEDRA study. Demographics and RA characteristics, risk factors for renal dysfunction (cardiovascular risks, medications) were collected in all participants. Results: Of the 970 recruited patients, 931 were analyzed (female gender: 79.6%, age: 57.8 years, disease duration: 11.1 years, DAS28-erythrocyte sedimentation rate: 3.1). 8.8% of patients had eGFR<60 ml/min/1.73m 2 . 9.9% of the patients had proteinuria (as defined by positive dipstick testing). In univariate analysis, age (p<0.001), presence of hypertension (p<0.001), systolic blood pressure (p=0.03), and Framingham Risk score (p<0.001) were associated with eGFR<60 ml/min/1.73m 2 . Renal dysfunction was not associated with gender (p=0.35), disease duration (p=0.91), disease activity (for DAS28-erythrocyte sedimentation rate: p=0.14, for SDAI: p=0.41, for CDAI: p=0.77) or RA medications. Two models of multivariate analysis were constructed: Model A, without the Framingham risk score revealing that age (OR: 1.05; IC95% [1.03-1.09]) and hypertension (OR: 2.5, IC95% [1.5-4.3]); were predictive of eGFR <60 ml/min/1.73m 2 Model B revealing that the Framingham risk score was predictive of eGFR <60 ml/min/1.73m 2 (OR 1.06, IC95% [1.03-1.09]). Conclusions: Renal impairment is quite common and associated with cardiovascular risk factors such as age, hypertension and Framingham risk score but not with disease activity. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4403